Valoración morfológica de la ubre y su relación con los rasgos morfométricos corporales de la cabra criolla Motilona de Norte de Santander, Colombia - Herrera-Cáceres, William (2022)
A study was carried out to determine the relationship between the morphological structure of the mammary gland and the morphometric body traits of 266 Motilona Creole goats from the Norte de Santander region (Colombia) belonging to systems oriented to the production of milk and meat. Morphological characteristics of the mammary gland were evaluated, such as: lateral and posterior view of the hind limbs, anterior insertion and depth of the udder, height and width of the posterior insertion of the udder, suspensory ligament, diameter and implantation of the teats. The body morphometric traits evaluated correspond to the length of the head and face, width of the head, height of the withers, width of the rump, longitudinal diameter, sternal and bicostal dorsum, length of the rump, perimeter of the cane and thorax. Additionally, the live weight of the animals was recorded. Pearson’s correlation coefficients were estimated. The results showed that there is a positive correlation between body morphometric traits and the live weight of the animals. The correlations between the live weight of the animals and the morphological traits of the mammary gland were low for the width of the posterior insertion of the udder and the suspensory ligament of the udder; however, for the other traits they were not significant. This study suggests that the Motilona goat population has a high degree of homogeneity in its traits and its morphological structure is appropriate for milk production